1983
DOI: 10.1136/bmj.286.6381.1851
|View full text |Cite
|
Sign up to set email alerts
|

Importance of markers of hepatitis B virus in alcoholic liver disease.

Abstract: To determine the importance of the presence of serological markers of hepatitis B virus infection in patients with alcohol related liver disease we compared cumulative alcohol intake and clinical and histological features in patients with markers of hepatitis B virus infection and in those without. Hepatitis B surface antigen (HBsAg) was detected in five (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
4

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 15 publications
(2 reference statements)
0
12
0
4
Order By: Relevance
“…Several studies (Saunders et al, 1983) have shown that patients with alcoholic cirrhosis showed evidence of past or current infection with HBV more commonly than did healthy nonalcoholic subjects (Bassendine et al, 1983;Goudeau et al, 1981;Inoue, 1977;Mills et al, 1981). A longitudinal study of hepatitis B surface antigenepositive healthy blood donors tested in Japan between 1972 and 1975 found that alcohol consumption greater than 27 g/day (duration of alcohol use not stated) was associated with more than a fivefold increase in the relative risk for development of HCC (Oshima et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (Saunders et al, 1983) have shown that patients with alcoholic cirrhosis showed evidence of past or current infection with HBV more commonly than did healthy nonalcoholic subjects (Bassendine et al, 1983;Goudeau et al, 1981;Inoue, 1977;Mills et al, 1981). A longitudinal study of hepatitis B surface antigenepositive healthy blood donors tested in Japan between 1972 and 1975 found that alcohol consumption greater than 27 g/day (duration of alcohol use not stated) was associated with more than a fivefold increase in the relative risk for development of HCC (Oshima et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Em vários estudos foram relatadas maiores prevalências de marcadores sorológicos de infecção pelo VHB em alcoolistas, quando comparados a controles ou à população geral, indicando que alcoolistas apresentam maiores riscos de adquirir esta infecção (1,3,6,13,16,18,20,24,25,27,28,29,30,31) . O comportamento da infecção pelo VHB em alcoolistas foi investigado em alguns trabalhos que apresentaram resultados controversos.…”
Section: Introductionunclassified
“…O comportamento da infecção pelo VHB em alcoolistas foi investigado em alguns trabalhos que apresentaram resultados controversos. Enquanto em alguns se observou que alcoolistas têm boa capacidade de clarear o VHB (1,3,17,25,28,31) , em outros foi relatado que alcoolistas têm dificuldade na eliminação deste vírus, provavelmente relacionada ao comprometimento do sistema imunológico ocasionado pelo álcool (16,24) . Também já foi descrito que pacientes com cirrose de causa alcoólica, quando têm um episódio agudo de HB, apresentam maiores riscos de desenvolverem a forma fulminante da doença (20) , e que alcoolistas portadores de infecção ativa pelo VHB (HBsAg positivo) podem ter mais chances de evoluir para a cirrose hepática (28,33,35) e/ou hepatocarcinoma (3,27,38) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Evidence of previous infection with hepatitis B virus was found in 20% of alcoholic cirrhotic patients, but this was not significantly different from those with fatty liver. 28 Important clues to the nature of the underlying drinking behaviour were obtained from the comprehensive alcohol assessment. Nearly all patients with alcoholic hepatitis or cirrhosis had a history of unremitting daily drinking, in contrast to those with fatty liver or fibrosis, whose drinking was often of the binge type.…”
Section: S99mentioning
confidence: 99%